Space production by migrants in China's urban villages the case of Beijing - Yang, Shiyu 1992- (transcript, 2023)
As China races towards modernity, its cities are experiencing an unprecedented surge in urbanisation, characterised by a relentless influx of migrants and sprawling expansion into suburban realms. Shiyu Yang draws upon Henri Lefebvre's influential theoretical framework and applies it to case studies of two urban villages in Beijing to examine how migrants shape the social production of space in these districts. With a wealth of first-hand material from the field, this study provides essential insights into the ongoing processes and social dynamics that resonate with scholars from cross-disciplinary urban studies as well as practitioners in governance and urban planning
Keywords: Beijing; China; City; Migration; Modernization; Sociology; Space; Urban Studies; SOCIAL SCIENCE / Sociology / Urban; Hochschulschrift